Dynamic stiffness analysis and isolation effectiveness of vibration isolation platform using pneumatic spring with auxiliary chamber - Vo , Ngoc Yen Phuong; Le, Thanh Danh; Nguyen, Minh Ky (Journal of Technical Education Science, 2019)
This paper will introduce a vibration isolation platform using the pneumatic cylinder with an auxiliary chamber (shorted the platform with auxiliary chamber). Firstly, the pressure model of the air spring including the pneumatic cylinder with the auxiliary chamber is analyzed. Instead of experiment, the Amesim software is used as the virtual prototype technology to verify the analysis solution of this spring. The result of this verification confirms that the analysis solution shows close agreement with the virtual simulation. Secondly, the complex dynamic stiffness of the vibration isolation platform is determined. The effects of the volume of the auxiliary chamber on the dynamic stiffness of the isolation platform are analyzed. Finally, the isolation performance of the platform with and without the auxiliary chamber is compared. The analysis result shows that the platform with auxiliary chamber can offer a promising isolation performance. This presentation furnishes a clear understand of the dynamic stiffness of an air spring with auxiliary chamber as well as the application of the air spring for designing isolation models.